2008
DOI: 10.1007/s00213-007-1067-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and repeated administration of salvinorin A on dopamine function in the rat dorsal striatum

Abstract: Rationale-Acute systemic administration of salvinorin A, a naturally occurring κ-opioid receptor (KOPr) agonist, decreases locomotion and striatal dopamine (DA) overflow.Objectives-Conventional and quantitative microdialysis techniques were used to determine whether salvinorin A infusion into the dorsal striatum (DSTR) decreases DA overflow by altering DA uptake or release. The influence of repeated salvinorin A administration on basal DA dynamics and cocaine-evoked alterations in DA overflow and locomotion wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 31 publications
0
72
2
Order By: Relevance
“…The maximum CPP response observed with the 40 g/kg dose was reduced by the CB 1 receptor inverse-agonist rimonabant as well as norBNI. In contrast to other studies (Zhang et al, 2005;Gehrke et al, 2008), 40 g/kg salvinorin A increased extracellular DA by ϳ150% of baseline for 140 min in the shell of the nucleus accumbens. Consistent with the salvinorin A-induced increase in extracellular DA observed in this study, intracerebroventricular salvinorin A supported self-administration behavior, an effect that was attenuated by either rimonabant or norBNI.…”
Section: Studies Examining Stress Mood and Rewardcontrasting
confidence: 95%
See 2 more Smart Citations
“…The maximum CPP response observed with the 40 g/kg dose was reduced by the CB 1 receptor inverse-agonist rimonabant as well as norBNI. In contrast to other studies (Zhang et al, 2005;Gehrke et al, 2008), 40 g/kg salvinorin A increased extracellular DA by ϳ150% of baseline for 140 min in the shell of the nucleus accumbens. Consistent with the salvinorin A-induced increase in extracellular DA observed in this study, intracerebroventricular salvinorin A supported self-administration behavior, an effect that was attenuated by either rimonabant or norBNI.…”
Section: Studies Examining Stress Mood and Rewardcontrasting
confidence: 95%
“…decreased extracellular DA but not 5-HT. Gehrke et al, (2008) extended these findings. This study showed that administration of salvinorin A (1.0 and 3.2 mg/kg i.p.)…”
Section: Studies Examining Stress Mood and Rewardmentioning
confidence: 53%
See 1 more Smart Citation
“…Also, κ-agonists attenuate the development and long-term expression of cocaine-induced behavioral sensitization following their repeated, intermittent administration [91] . These effects most likely result from the inhibition of limbic DA release after acute administration of κ-agonists [34,88,92,93] . However, there is paradoxical evidence that continuous or prior exposure to κ-agonists can potentiate the rewarding effects of cocaine under stress conditions and stress-induced reinstatement [36,94,95] .…”
Section: Potential Therapeutic Applications Of κ-Opioid Agonists In Pmentioning
confidence: 99%
“…These receptors not only have traditional G i/o -negative regulatory effects on adenylate cyclase activity but also couple to mitogen-activated protein kinase pathways and inward rectifying potassium channels (Bruchas et al, 2010;Al-Hasani and Bruchas, 2011). Although the mechanisms of stress-induced reinstatement of drug seeking and drug reward are complex, it has been shown that stress causes dynorphin release and KOR activation within both dopaminergic and serotonergic nuclei (Carlezon et al, 2006;Ebner et al, 2010;Gehrke et al, 2008;Land et al, 2008;Zhang et al, 2005). This KOR activation results in reduced dopamine and serotonin levels, contributing to the dysphoria-like behavioral responses that drive reinstatement of drug seeking and reward behaviors.…”
Section: Introductionmentioning
confidence: 99%